Teacher’s Self-perception of Resilience among Junior High School English Teachers in Gunungkidul Regency - Ranggi Mulia Bestari; Ouda Teda Ena; Consilianus Laos Mbato (JELLT (Journal of English Language and Language Teaching), 2022)
Being resilient increases teachers’ quality in their educational process. Resilience becomes one of the professional matters. Resilience means bouncing back or returning and accepting necessity, so teachers adapt to difficulties. In teaching, teachers might face many challenges in many aspects. Novice teachers and experienced teachers face difficulties, but they have their own beliefs about resilience The aim of this research was to investigate teachers’ self-perception of resilience. The researchers applied mixed methods to collect and analyze the data. The researchers used close-ended and open-ended of questionnaire for the instrument. There were 52 participants. The participants were English teachers who joined an English teacher’s discussion group in Gunungkidul Regency. The result of the research is novice teachers and experienced teachers in the resilience scale more dominant have a moderate level. Based on the interview, the experienced teachers have passed the challenges, not only about in teaching process but their process of being resilient.